The ethical responsibility to continue investigational treatments of research participants in situation of armed conflicts, economic sanctions or natural catastrophes - Kerpel-Fronius, Sandor; Kurihara, Chieko; Crawley, Francis P.; Baroutsou, Varvara; Becker, Sander; Franke-Bray, Brigitte; Matsuyama, Kotone; Naseem, Shehla; Schenk, Johanna (Frontiers in Medicine, 2022)
This paper discusses the effects of armed conflict, economic sanctions, and natural catastrophes on ongoing clinical trials. We suggest that • research participants already receiving trial medication in such disruptive situations are to be considered highly vulnerable due to their medical dependency for ongoing treatment according to the approved clinical study protocol • we conclude that finishing ongoing trial treatments according to approved or amended protocols should be considered to be an ethical obligation of trial sponsors irrespective whether trial disruption is due to war, economic sanctions, or natural catastrophes • it is important to devote more attention to the ethical challenges raised by such fundamentally disruptive situations to clinical trials generally in any region of the world